The Relationships between Neutrophil/Lymphocyte Ratio and Child-Turcotte-Pugh Classification in Assessing Severity of Liver Cirrhosis - Griselda Griselda; Kemas Ya'Kub Rahadiyanto; Rachmat Hidayat (HM Publisher, 2019)
Background Liver cirrhosis is a disease with high morbidity and mortality in Indonesia. The Child-Turcotte-Pugh classification is a noninvasive parameter to assess severity of liver cirrhosis. Meanwhile, the neutrophil/lymphocyte ratio can reflect person's immunity to liver cirrhosis. This study was conducted to determine the agreement between neutrophil/lymphocyte ratio and Child-Turcotte-Pugh classification in assessing severity of liver cirrhosis. Methods Analytical observational study with Cohen’s Kappa agreement test was conducted in 86 liver cirrhosis patients. Data was retrieved by observing the medical records. Neutrophil count, lymphocyte count, hepatic encephalopathy, ascites, albumin, bilirubin, and INR were all recorded. Documented variables were analyzed by the Cohen’s Kappa agreement test. Results In Cohen’s Kappa agreement test, there was moderate agreement between neutrophil/lymphocyte ratio and Child-Turcotte-Pugh classification in all samples (κ = 0.591 and p <0.001). Agreement between neutrophil/lymphocyte ratio and Child-Turcotte-Pugh classification based on age and gender was found to be κ = 0.777 at age ≤45 years, κ = 0.532 at age >45 years, κ = 0.682 in male, and κ = 0.445 in female (p <0.001). The highest agreement is the substantial agreement between neutrophil/lymphocyte ratio and Child-Turcotte-Pugh classification obtained at age ≤45 years (κ = 0.777 and p <0.001) and male (κ = 0.682 and p <0.001). Conclusion There is moderate agreement between neutrophil/lymphocyte ratio and Child-Turcotte-Pugh classification in assessing severity of liver cirrhosis. Substantial agreement obtained at age ≤45 years and male gender. Keywords: Neutrophil/Lymphocyte Ratio, Child-Turcotte-Pugh, Liver Cirrhosis